Large but Nonstenotic Carotid Artery Plaque in Patients With a History of Embolic Stroke of Undetermined Source. Issue 12 (December 2018) - Komatsu, Teppei; Iguchi, Yasuyuki; Arai, Ayumi; Sakuta, Kenichi; Sakai, Kenichiro; Terasawa, Yuka; Mitsumura, Hidetaka; Matsushima, Masato
Abstract : Background and Purpose—: This study's objective is to determine if nonstenotic carotid plaque of <50% luminal narrowing predominantly develops ipsilateral rather than contralateral to the stroke site. Methods—: This was a cross-sectional observational study. We identified consecutive patients with anterior circulation embolic stroke of undetermined source (ESUS), excluding stroke in multiple vascular territories. Using ultrasonography, we measured the internal carotid plaque size and stenosis for each patient. We dichotomized the plaque size at several predefined thresholds and calculated the frequency of the plaque size and morphology above each threshold ipsilateral versus contralateral to the stroke site. Results—: We included 53 patients with unilateral anterior circulation ESUS. Initially, we found that plaque with a thickness ≥1.5 mm was present ipsilateral to the stroke site in 59% of the patients, and present contralateral to the stroke site in 42% of the patients (31/53 versus 22/53 patients; P =0.049). Plaque with low echo likewise had a similar prevalence when present ipsilateral (9%) and contralateral (4%) to the stroke site (5/53 versus 2/53; P =0.25). Conclusions—: Internal carotid artery plaque with a thickness ≥1.5 mm but that is nonstenotic (<50%) is considerably more common when ipsilateral to the ESUS site than when contralateral to the ESUS site, especially in plaque with a thickness ≥2.6 mm. Large but nonstenotic carotid artery plaque is associated with anterior circulation ESUS. Abstract : Supplemental Digital Content is available in the text.